Application of remote sensing techniques in lithologic mapping of Djanet Region, Eastern Hoggar Shield, Algeria - Nemmour-Zekiri, Dalila; Oulebsir, Fatiha (Arabian journal of geosciences, 2020)
Application of remotely sensed data in geological mapping has been the subject matter of many studies in the last decades. The optimal exploitation of high spatial resolution satellite imagery can contribute to the improvement of the geological map, particularly when it comes to mapping in arid and desert areas where outcrops are often inaccessible. Djanet area lies in Eastern Hoggar Shield, Algeria. It is characterized by rather high corrugated reliefs and this makes it difficult to collect samples or even get field information from the entire region. The study covers the terrane of Djanet and part of the terrane of Edembo. In addition, this region is probably one of the least explored areas of Hoggar. This is why different remote sensing techniques have been used to make geologic mapping faster and more efficient. Processing of Landsat-7 ETM+ images covering the Djanet region includes various treatments ranging from contrast enhancements to spectral enhancements, and using images in 742 RGB color compositions, calculation processing of band ratios (3/1, 5/4, 7/5) and the (5/7, 2/1, 4/2) and the application of the directional filters, according to the orientations ranging from N000 up to N180E, with a semi-automatic approach for the extraction of lineaments to establish two maps, a lithological map and another linear map. The correlation of these maps with the field data allowed us to check the validity and the correspondence of the different facies and especially to clarify the lithological contours and the identification of the majority of the tectonic accidents derived from the analysis of Landsat satellite data. The geological map obtained gives another image of the region studied and provides new information on the contacts of the lithological units and the structural diagram.